Managing high milk-producing herds IX. Raising dairy heifers and steers: a business. Surviving GATT, NAFTA, and the 1995 farm bill - John E. Shirley (Kansas Agricultural Experiment Station Research Reports, 1994)
The primary focus of the dairy industry in Kansas has been the milking herd. However, dairy heifer replacements and dairy steers offer income opportunities that have been largely ignored by some Kansas dairy producers. The 1994 Dairy Day program highlights these programs as potential profit centers. An "opportunity cost" analysis comparing the economic returns from your present enterprises with the potential returns from a dairy heifer or steer enterprise might propel you into a new career or enhance the profitability of your total operation.; Dairy Day, 1994, Kansas State University, Manhattan, KS, 1994;
Keywords: Dairy Day; 1994; Kansas Agricultural Experiment Station contribution; no. 95-141-S; Report of progress (Kansas Agricultural Experiment Station); 716; Raising dairy heifers; Business; 1995 Farm bill